Project-based learning (PjBL) strategies with gamification - Putri Fadilla Azzahra Fazarini; Yerry Soepriyanto; Henry Praherdhiono (Inovasi Kurikulum, 2024)
This research aims to develop and test the effectiveness of the Project-Based Learning (PjBL) learning model integrated with gamification (G-PJBL) to increase student engagement and learning outcomes in Graphic and Visual Media courses. The background to this research is the low graduation rate of students in this course due to the diverse backgrounds and abilities of students. PjBL research with Gamification activities uses the ASSURE development model, which contains six stages. Construction is carried out sequentially according to the plans that have been made. Research data was obtained from validation by learning design experts, observations during learning, and student learning outcomes. The development of PjBL with gamification activities has had a positive impact on increasing student engagement and motivation. The research results show that the well-structured G-PJBL syntax follows student needs. Validation by learning design experts shows that the learning design is feasible. In addition, the research results show that G-PJBL can increase student engagement and learning motivation and improve their learning achievement. This model can be applied to other courses that require student involvement and creativity.   Abstrak Penelitian ini bertujuan untuk mengembangkan dan menguji efektivitas model pembelajaran Project-Based Learning (PjBL) yang diintegrasikan dengan gamifikasi (G-PJBL) untuk meningkatkan keterlibatan dan hasil belajar mahasiswa pada mata kuliah Media Grafis dan Visual. Latar belakang penelitian ini adalah rendahnya tingkat kelulusan mahasiswa pada mata kuliah tersebut karena beragamnya latar belakang dan kemampuan mahasiswa. Penelitian PjBL dengan kegiatan Gamification menggunakan model pengembangan ASSURE yang berisi 6 tahapan yang digunakan. Pembangunan dilakukan secara berurutan sesuai dengan rencana yang telah dibuat. Data penelitian diperoleh dari validasi ahli desain pembelajaran, observasi selama pembelajaran, dan hasil belajar mahasiswa. Pengembangan PjBL dengan kegiatan gamification memberikan dampak positif terhadap peningkatan engagement dan motivasi mahasiswa. Hasil penelitian menunjukkan bahwa sintaks G-PJBL yang dikembangkan telah sesuai dengan kebutuhan mahasiswa dan terstruktur dengan baik. Validasi ahli desain pembelajaran menunjukkan bahwa desain pembelajaran layak untuk diterapkan. Selain itu, hasil penelitian menunjukkan bahwa G-PJBL mampu meningkatkan keterlibatan dan motivasi belajar mahasiswa, serta meningkatkan prestasi belajar mereka. Model ini dapat diterapkan pada mata kuliah lain yang membutuhkan keterlibatan dan kreativitas mahasiswa. Kata Kunci: berbasis proyek; gamifikasi; PjBL; strategi pembelajaran; teknologi pendidikan